The Relationship between Resilience and Care Burden among Parents of Students with Intellectual Disability in Golestan Province, Iran, in 2016 - Fatemeh Hassanzadeh; Hamid Hojjati (Vesnu Publications, 2017)
Introduction: Children with intellectual disabilities sometimes disrupt the mental health of the family and cause serious damages in their parents. Consideration of the mental health of parents of exceptional children is important due to the psychological, social, and financial burden of care and increased care burden on families of children with intellectual disabilities. Materials and Methods: This was a descriptive-correlation study. The subjects consisted of 200 parents of students in special schools of Golestan Province, Iran, in 2016. The participants were selected through multistage random sampling method. A demographic information questionnaire, the Conner-Davidson Resilience Scale (CD-RISC), and Elmstahl's Caregiver Burden Scale were used to collect data. The collected data were analyzed using descriptive and inferential statistics in SPSS software at the significance level of P < 0.05. Results: In this study, the resilience and burden of care scores of parents of children with intellectual disabilities were 51.86 ± 17.27 and 56.89 ± 14.27, respectively. Simple linear regression test showed a significant relationship between resilience and burden of care [B = 0.32, Beta = 0.39, P < 0.01, %95 CI: -6 (-4.2 to -8.1)]; with 1 degree decrease in resilience, the burden of care score will increase 0.3 points. Conclusion: In this study, the burden of care was higher and resilience was lower than average and resilience of parents of students with intellectual disabilities could be increased with reduction in the amount of burden of care. Among the predictive variables, the effect of income on the burden of care was evident to a greater extent in parents of children with intellectual disabilities compared to other variables. This indicates that the burden of care can be reduced and resilience can be increased by raising income levels and economic well-being. Therefore, it is suggested that the necessary economic and counseling measures be taken to reduce the burden of care.